Regional industrial development in the Russian Federation under sanctions and restrictions - A. A. Shatsky (Управление)
The article presents an assessment of the main statistical indicators on the effectiveness of the industrial production process development in the Russian regions in recent years. The development of Russian industrial production in the regions in modern conditions and the prospects for its development are studied. The introduction provides an overview of the scientific literature of research economists studying the problem of industrial production, and formulates the goals and objectives of the study. In the work, the author characterizes the state of development of industrial production in the Russian regions, depending on the regional development of the economy under sanctions. An assessment of the indicators of industrial development, the main economic indicators of the activity of industrial enterprises was carried out, an analysis of the methods of both Russian and foreign scientists who took part in the study of this problem was made. The study focuses on indicators characterizing the development of industrial production in Russia and its regions. At the end of the article, it was concluded that in the future it is necessary to continue the transformation of the industrial production of the regional administration, and a forecast for the long-term development of industrial production in Russia was made.